Analysis of Factors Causing Work Accidents in Steel Plate Production with FTA and PDCA Methods at PT. XYZ - M. H. N. Islamsyah; Rizqi Novita Sari (Yayasan Kita Menulis, 2025)
The identification of work accidents in the steel plate production process poses a serious risk to workers and disrupts operational activities. This research analyzes the factors causing work accidents at PT XYZ in the steel plate production process using the Fault Tree Analysis (FTA) method and the Plan-Do-Check-Act (PDCA) method. FTA is applied to identify and decipher the root causes of accidents, while PDCA serves as a framework for continuous improvement. Data were collected through accident reports, observations. The results showed that human error, including being pinched by a plate, hit by a ganco, and exposed to sparks were the main contributors to the occurrence of accidents. Through the PDCA cycle, several preventive measures were proposed, including enhancing worker training, improving equipment maintenance, and strengthening safety protocols. This study provides actionable insights to improve workplace safety and reduce the risk of accidents in the steel plate production process.